2009
DOI: 10.1007/s15010-009-9034-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Procalcitonin-Guided Treatment in Patients with Infections: a Systematic Review and Meta-Analysis

Abstract: Based on the results of this meta-analysis, it would appear that an algorithm based on serial PCT measurements would allow a more judicious use of antibiotics than currently occurs during the traditional treatment of patients with infections. PCT-guided antibiotic treatment appears to be safe and may also improve clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 42 publications
3
64
0
2
Order By: Relevance
“…The measurement of a series of PCT levels has consistently been described as useful for the evaluation of therapeutic success [7,21]. Hohn et al demonstrated these effects, even among routine clinical populations [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of a series of PCT levels has consistently been described as useful for the evaluation of therapeutic success [7,21]. Hohn et al demonstrated these effects, even among routine clinical populations [22].…”
Section: Discussionmentioning
confidence: 99%
“…PCT Reduction: PCT reduction within 12 days of the first pathological PCT measurement PCT reduction was considered to have occurred when the PCT value was 80% lower than the highest value recorded, or 0.25 ng/ml; these definitions have been used in various scientific publications and ensure practical limits to evaluate the effect of an antibiotic [7,11].…”
Section: Episodementioning
confidence: 99%
See 1 more Smart Citation
“…However, other authors reported lower diagnostic accuracy, with sensitivity as low as 41% (22) and specificity as low as 24% (23). PCT could be an interesting tool to discontinue antimicrobial therapy safely in the ICU according to recent studies (24,25), and as such could represent a potential candidate as a POCT tool. POCT to laboratory testing correlation seems to be sufficient (26), but there is no available data regarding its use for VAP, and few results are available for communityacquired pneumonia (27).…”
Section: Introductionmentioning
confidence: 99%
“…The use of PCT supplies caregivers with added information, which, in principle, enables them to improve the selection of patients for treatment, the timing of treatment initiation, and the overall duration of treatment [21,28,32,33,35,[41][42][43][44][45][46][47]. Insofar as caregivers change their care management and treatment strategies in response to the new information (relative to the usual standard course of action), there are implications for changes in outcomes, both in terms of treatment costs and health status [14,33,35].…”
Section: Introductionmentioning
confidence: 99%